Preparing Public Health Professionals to Make Evidence-Based Decisions: A Comparison of Training Delivery Methods in the United States - Jacob, Rebekah R.; Duggan, Kathleen; Allen, Peg; Erwin, Paul C.; Aisaka, Kristelle; Yang, Samuel C.; Brownson, Ross C. (Frontiers in Public Health, 2018)
Background. Evidence-based decision making (EBDM) in health programs and policies can reduce population disease burden. Training in EBDM for the public health workforce is necessary to continue capacity building efforts. While in-person training for EBDM is established and effective, gaps in skills for practicing EBDM remain. Distance and blended learning (a combination of distance and in-person) have the potential to increase reach and reduce costs for training in EBDM. However, evaluations to-date have focused primarily on in-person training. Methods. A quasi-experimental pre-post design was used to compare gaps in skills for EBDM among public health practitioners who received in-person training, distance and blended learning, and controls. Nine training sites agreed to replicate a course in EBDM with public health professionals in their state or region. Courses were conducted either in-person (n=6) or via distance or blended learning (n=3). All training participants, along with controls, were asked to complete a survey before the training and six months post-training. Paired surveys were used in linear mixed models to compare effectiveness of training compared to controls. Results. Response rates for pre and post surveys were 63.9% and 48.8% for controls and 81.6% and 62.0% for training groups. Participants who completed both pre and post surveys (n=272; 84 in-person, 67 distance or blended, and 121 controls) were mostly female (89.0%) and about two-thirds (65.3%) were from local health departments. In comparison to controls, overall gaps in skills for EBDM were reduced for participants of both in-person training (β=-0.55, SE=0.27, p=0.041) and distance or blended training (β=-0.64, SE=0.29, p=0.026). Conclusions. This study highlights the importance of using diverse methods of learning (including distance or blended in-person approaches) for scaling up capacity building in EBDM. Further exploration into effective implementation strategies for EBDM trainings specific to course delivery type and understanding delivery preferences are important next steps.